2021
DOI: 10.1002/hep.31912
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Phylodynamics of Hepatitis C Among People Who Inject Drugs in India

Abstract: BaCKgRoUND aND aIMS: Implementing effective interventions for HCV requires a detailed understanding of local transmission dynamics and geospatial spread. Little is known about HCV phylodynamics, particularly among high-burden populations, such as people who inject drugs (PWID).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Sequence analysis of fast evolving viruses such as HCV was shown to be efficient method for viral transmission tracing [ 16 , 17 , 49 , 51 ]. Phylogenetic analysis demonstrated that 27 (9.0%) of Croatian HCV sequences had a presumed epidemiological link with another sequence and classified into 13 transmission pairs or clusters which were the most common in GT3a, while IDU was shown to be a risk factor statistically associated with clustering.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sequence analysis of fast evolving viruses such as HCV was shown to be efficient method for viral transmission tracing [ 16 , 17 , 49 , 51 ]. Phylogenetic analysis demonstrated that 27 (9.0%) of Croatian HCV sequences had a presumed epidemiological link with another sequence and classified into 13 transmission pairs or clusters which were the most common in GT3a, while IDU was shown to be a risk factor statistically associated with clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Hackman et al (2020) found that 46% of 820 community recruited IDU in Baltimore had genetically linked HCV infections with an average cluster size of 2–3 patients [ 49 ]. Clipman et al (2021) analysed 483 HCV sequences from IDU in India and found transmission cluster prevalence of 28.8% with a median cluster size of three individuals [ 16 ]. Cluster analysis showed that younger age (<35 years) was significantly associated with being in a cluster, similarly to our study [ 16 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic trees based on nucleotide sequences were generated using the bootstrap method (1,000 times) under a GTR+G model. According to previous studies of HIV-1 and HCV ( 72 ), we used a stringent threshold of 1% genetic distance for the detection of transmission clusters (TC) of pegiviruses.…”
Section: Methodsmentioning
confidence: 99%